Efficacy of platelet concentrates in bone healing: A systematic review on animal studies – Part B: Large-size animal models. (19th May 2018) - Marcazzan, Sabrina; Taschieri, Silvio; Weinstein, Roberto Lodovico; Del Fabbro, Massimo
Abstract: In the presence of large bone defects, delayed bone union, or nonunion and fractures, bone reconstruction may be necessary. Different strategies have been employed to enhance bone healing among which the use of autologous platelet concentrates (APCs). Due to the high content of platelets and platelet-derived bioactive molecules (e.g., growth factors, antimicrobial peptides), they are promising candidates to enhance bone healing. However, both preclinical and clinical studies produced contrasting results, mainly due to a high heterogeneity in study design, objectives, techniques adopted, and outcomes assessed. The aim of the present systematic review was to evaluate the efficacy of APCs in animal models of bone regeneration, considering the possible factors that might affect the outcome. An electronic search was performed on MEDLINE and Scopus databases. Comparative animal studies with a minimum follow up of 2 weeks, at least five subjects per group and using APCs for regeneration of bone defects were included. Articles underwent risk of bias assessment and quality evaluation. Fifty studies performed on six animal species (rat, rabbit, dog, sheep, goat, mini-pig) were included. The present part of the review considers studies performed on small ruminants, dogs, and mini-pigs (14 articles). The majority of the studies were considered at low risk of bias. In general, APCs' adjunct positively affected bone regeneration. Animal species, platelet and growth factors concentration, type of bone defect and of platelet concentrate used seemed to influence their efficacy in bone healing. However, sound conclusions were not drawn since too few studies for each large-size animal model were included. In addition, characterization of APCs' content was performed only in a few studies. Further studies with a standardized protocol including characterization of the final products will provide useful information for translating the results to clinical application of APCs in bone surgery.